2012
DOI: 10.1177/1534734612448384
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Three Years of Teamwork on Critical Limb Ischemia in Patients With Diabetes and Foot Lesions

Abstract: To evaluate the outcomes of a multidisciplinary team working on diabetic foot (DF) patients with critical limb ischemia (CLI) in a specialized center, the authors retrospectively traced all the patients admitted in their department in 3 consecutive years with a diagnosis of CLI. From January 2006 to December 2008, 245 consecutive DF patients with CLI according the TransAtlantic interSociety Consensus II criteria were included in the study. Treatment strategy was decided by a team of diabetologists, intevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…One hundred eighty‐two full‐text articles were assessed for eligibility, and 133 (65 reviews, eight studies of duplicated population, and 60 studies with data that cannot be extracted) of them were removed since they did not meet our selection criteria. Finally, 49 articles were included in our meta‐analysis after full‐text review …”
Section: Resultsmentioning
confidence: 99%
“…One hundred eighty‐two full‐text articles were assessed for eligibility, and 133 (65 reviews, eight studies of duplicated population, and 60 studies with data that cannot be extracted) of them were removed since they did not meet our selection criteria. Finally, 49 articles were included in our meta‐analysis after full‐text review …”
Section: Resultsmentioning
confidence: 99%
“…A multidisciplinary team approach to the diabetic foot has been widely recognized to lead to increased rates of wound healing, decreased major limb amputation levels, lower healthcare costs, and improved patient care (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). However, a potentially underappreciated component of this team is that of psychiatry.…”
mentioning
confidence: 99%
“…The treatment strategy was decided jointly by a team including diabetologists, radiologists, and vascular surgeons (Scatena et al. ). Similarly, Peterson and colleagues concluded that strengthening collaboration among providers reduced mean glycated hemoglobin (HbA1c) across 12 pediatric diabetes centers in Sweden.…”
Section: Conceptual Frameworkmentioning
confidence: 99%